PEMBUATAN SISTEM PENGELOLAAN DATA BERBASIS APLIKASI DESKTOP DI KANTOR YAYASAN BANTUAN ANAK INDONESIA - I Putu Rizky Pratama Putra; Gst. Ayu Vida Mastrika Giri; I Putu Gede Hendra Suputra (Jurnal Pengabdian Informatika, 2026)
The data management at Yayasan Bantuan Anak Indonesia, which has been conducted manually, has encountered several challenges such as inefficiency. To address these issues, a desktop-based data management system was developed. This system is designed to integrate all data related to foster children, foster parents, and the programs run by the foundation. The development of this system went through several stages, from needs analysis to implementation and training. The result of this project is a desktop application that facilitates the foundation's staff in managing data, monitoring the status of foster children and foster parents, and supporting faster and more accurate decision-making